Eemian and post-Eemian fluvial dynamics in the Lesser Caucasus. (1st July 2018) - von Suchodoletz, Hans; Gärtner, Andreas; Zielhofer, Christoph; Faust, Dominik
Abstract: Mountain regions such as the Lesser Caucasus are a focus of ongoing environmental changes. To understand their future evolution, information about their former geomorphic and environmental dynamics is required. The former fluvial dynamics derived from fluvial sediment archives can offer such insights. However, the fluvial dynamics of the Lesser Caucasus since the Eemian interglacial have not been systematically investigated so far. Thus, we have studied late Pleistocene and Holocene sediments of several rivers originating from the central Lesser Caucasus. The studied rivers show a mostly coherent record of fluvial dynamics: Minor aggradation occurred during early Marine Isotope Stage (MIS) 5, incision during late MIS 5 or early MIS 4, intensive silty aggradation at least during late MIS 3, incision during early MIS 2, coarse-grained aggradation probably during some millenia until ca. 19 ka, and aggradation ca. 14-13 ka. Following incision around the Pleistocene/Holocene transition, aggradation resumed around 6.0, 3.4 – 2.0 and 0.5 – 0.15 cal. ka BP. Generally, periods of aggradation, incision and stability could be linked with regional climatic or anthropogenic influences on regional landscape stability and water availability. The fluvial dynamics of the central Lesser Caucasus mostly differed even between neighbouring regions, and only in cases of significant hemispheric climatic fluctuations as around 20 ka, during the Pleistocene/Holocene transition or the Little Ice Age, were similar over-regional fluvial patterns observed. This demonstrates the individual character of river systems especially in mountain regions such as the southern Caucasus with strong geoecological gradients. Thus, to understand the former landscape dynamics of mountain landscapes, investigations of fluvial sediment archives on a regional to sub-regional scale are necessary. Highlights: First study that investigates fluvial dynamics in Lesser Caucasus since Eemian interglacial. Most time the since Eemian the fluvial dynamics in the Lesser Caucasus differed from those even in neighbouring regions. This shows the individual character of rivers especially in ecologically and geomorphologically diverse mountain regions.